2004
DOI: 10.1111/j.1432-2277.2004.tb00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to anti-CD45RB-induced tolerance in NOD mice: mechanisms involved

Abstract: While great advances have been made in the success of islet transplantation to cure autoimmune diabetes, this protocol remains limited by our inability to induce donor-specific tolerance within the recipient. The profound resistance of the NOD mouse to tolerance-inducing regimens that are routinely successful in other strains further defines the imposing barriers that must be surmounted. Herein, we have assessed the utility of anti-CD45RB therapy to induce tolerance to allografts in C57BL/6 and NOD-strain mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…42,43 Anti-RB treatment is useful as an immunotherapeutic agent and induces transplant tolerance. 39,[44][45][46][47] It must be stressed that B cells play a critical role in these processes. 48 Therefore additional studies into the impact of CD45RB ligation on the surface of B cells are needed.…”
mentioning
confidence: 99%
“…42,43 Anti-RB treatment is useful as an immunotherapeutic agent and induces transplant tolerance. 39,[44][45][46][47] It must be stressed that B cells play a critical role in these processes. 48 Therefore additional studies into the impact of CD45RB ligation on the surface of B cells are needed.…”
mentioning
confidence: 99%
“…Initial studies indicated a role of tolerogenic dendritic cells in this model (12). In addition, we have recently studied the effect of anti-CD45RB therapy in NOD mice and found that NOD mice are resistant to anti-CD45RB-induced transplant tolerance, even in the absence of autoimmunity (13). Because of the critical role played by B lymphocytes as APCs in autoimmune disease (14), we hypothesized that B cells may play a requisite role in tolerance induced by anti-CD45RB.…”
mentioning
confidence: 99%
“…Consistent with this process, islet-specific autoantibodies, particularly ones reactive with insulin, are recognized as sensitive indicators of disease (20 -26). To date, tolerance-inducing therapies initiated after the appearance of IgG anti-insulin autoantibodies fail to halt disease progression (27,28). Thus, earlier predictive methods are required to maintain or restore lymphocyte tolerance before ␤ cell destruction.…”
mentioning
confidence: 99%